Reduction of dipyrido ureas via 6-Alkyloxydipyrido(1,2-c;2´,1´-e)imidazolium salts - Kunz, Doris; Deißler, Christine; Gierz, Verena; Rominger, Frank; Oeser, Thomas (Zeitschrift für Naturforschung. B, a journal of chemical sciences, 2010)
Dipyrido uronium salts can readily be synthesized by alkylation of dipyrido ureas with Meerwein’s reagent. Compared to the corresponding ureas, the uronium salts are more reactive towards basic or reducing agents like metal hydrides. Reactivity studies show that the uronium salts can react as alkylating agents towards DMSO, DBU and NaOEt along with release of the respective dipyrido ureas. In contrast, reduction of the dipyrido uronium salts with sodium borohydride or sodium trimethoxyborohydride in dry and degassed acetonitrile leads to the imidazolium salts 7a and 7b in moderate yields. Analysis of the by-products reveals an in situ carbene formation which can be reversed by using degassed but wet acetonitrile as solvent. The yield of 7b was increased significantly by these means. Graphical Abstract Reduction of Dipyrido Ureas via 6-Alkyloxydipyrido[1,2-c;2´,1´-e]imidazolium Salts
Elektronische Reproduktion der Druckausgabe
Im Titel steht der Ausdruck 1,2-c;2´,1´-e in eckiger Klammer
Gesehen am 08.03.2023